Quality of care for dual eligible beneficiaries in the oncology care model - Xinyu Liang; Ziwei Zhu; Kassem Faraj; Vahakn B. Shahinian; Brent K. Hollenbeck; Lindsey A. Herrel (Cancer Medicine)
Abstract Introduction Dual eligible beneficiaries are a vulnerable population who often experience inferior access to care and outcomes compared to non‐dual eligible beneficiaries. The Oncology Care Model (OCM) is an alternative payment model that aims to improve coordination and quality of care in beneficiaries receiving chemotherapy and thus may improve care for dual eligible beneficiaries with cancer. Methods We used 100% Medicare claims data from 2014 through 2019 and included beneficiaries with bladder, breast, esophageal, colorectal, kidney, lung, pancreatic, or prostate cancer receiving chemotherapy. We constructed multivariable difference‐in‐differences regression models to evaluate the effect of OCM participation on healthcare utilization and quality of care at the end‐of‐life among dual eligible beneficiaries. We also compared healthcare utilization and quality of care outcomes to non‐dual eligible beneficiaries. Results We identified 3,043,944 episodes of care among 1,260,892 unique Medicare beneficiaries. Ten percent of all beneficiaries (n = 126,758) were dual eligible and 64,087 (22%) of episodes among dual eligible patients were in an OCM participating practice. We noted no effect of OCM participation on healthcare utilization or end‐of‐life quality of care for dual eligible beneficiaries. However, we observed higher rates of hospitalization, emergency department visits, intensive care unit stays, and a lower number of office visits among dual eligible beneficiaries compared to non‐dual eligible beneficiaries. Conclusions Participation in OCM was not associated with improvements in quality of care or healthcare utilization for dual eligible beneficiaries. Dual eligible beneficiaries experience lower quality of care across several measures compared to non‐dual eligible beneficiaries. Focused policies and incentives may be necessary to address disparities within emerging health reforms.